Miniaturized Wide Scanning Angle Phased Array Using EBG Structure for 5G Applications - Xiumei Shen; Kun Xue; Xinggang Tang; Yuqi He (International Journal of Antennas and Propagation)
This article presents a miniaturized wide-angle scanning phased array for fifth-generation (5G) application. A subarray of two closely packed patch antennas on electromagnetic bandgap structure (EBG) ground with the operating bandwidth of 26–29 GHz is used as the basic module of the linear array, which contains four equally spaced subarrays. The existence of the EBG ground enables the array to be compact in size (3.2 × 0.6 × 0.12λL3), yet the mutual coupling between each element can reach to more than 22 dB within the whole band of interest. The EBG structures also contribute to the wide element radiation pattern of the aperiodic array and consequently the wide scanning angle performance of the array. The range of the main beam scan with EBG structure can reach from −70° to 70° with more than 6 dB side lobe levels (SLLs) at 26.5 GHz with 3 dBi scanning gain loss. This proposed method enabling the array to be compact and wide in scanning angle is very attractive for 5G mobile terminal applications.